Peningkatan Pengetahuan tentang Gizi di Masa Pandemi untuk Pencegahan Covid-19 - Sunarti Sunarti; Rachmawati Widyaningrum; Dyah Suryani; Hesti Khofifah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Nutritional fulfillment is one of the essential factors to prevent the Covid-19 disease. The term balanced nutrition consists of several points: balanced consumption of staple food, the source of protein, fruit, and vegetables, and also drinking an adequate amount of water. Several specific nutrients are also involved in strengthening the immune system, such as vitamin A, C, E, B6, folic acid, zinc, selenium, and iron. The balanced diet practices are affected by nutrition knowledge and further underlined the importance of an educational approach to knowledge improvement of its principles to prevent Covid-19 disease. The intervention conducted through an online meeting platform with a pre-post test was applied to measure the level of knowledge. There were 92 participants in this international event, with the knowledge score improvement was 25% higher than the pre-test mean score. The highest rose was in the vegetables daily intake recommendation and the highest vitamin C source. In conclusion, sustainable educational intervention is important to improve the community’s knowledge about a balanced diet that plays a role in Covid-19 disease prevention.